Qualitative Insights into Key Angelman Syndrome Motor Related Concepts Reported by Caregivers-A Thematic Analysis of Semi-Structured Interviews - Miranda Rogers; Stéphane Motola; Yacine Bechichi; Céline Cluzeau; Tanguy Terray; Allyson Berent; Jennifer Panagoulias; Jessica Duis; Damien Eggenspieler; Laurent Servais (MDPI AG, 2023)
Previous patient-centered concept models of Angelman syndrome (AS) are integral in developing our understanding of the symptoms and impact of this condition with a holistic perspective and have highlighted the importance of motor function. We aimed to develop the motor and movement aspects of the concept models, to support research regarding motor-related digital outcomes aligned with patients' and caregivers' perspectives. We conducted a qualitative analysis of semi-structured interviews of 24 caregivers to explore AS motor-related features, factors influencing them and their impact on patients and caregivers.The most impacted motor features were gait, walking and stair-climbing. Half of caregivers ranked motor symptoms as one of the most burdensome symptoms of AS. Caregivers frequently reported physical therapy, motivation, medical management and age as factors influencing motor function in AS and reported that impaired motor function affected both patients and caregivers. Measures of lower-limb motor function were identified as relevant to monitor drug effectiveness in AS. Caregivers discussed expected benefits of a digital outcome and potential issues with wearable technology in the context of AS. We propose a new motor function patient-centered concept model, providing insights for the development of relevant, motor-related, digital outcomes in AS.